Solitary Plasmacytoma of the Mesentery: A Systematic Clinician’s Diagnosis - Georgia Mitropoulou; Adamantia Zizi-Sermpetzoglou; Hippokrates Moschouris; Athanasios Kountourogiannis; Despoina Myoteri; Dionysios Dellaportas (Case Reports in Oncological Medicine)
Introduction. Plasmacytoma is an uncommon plasma cell neoplasm and its localized form is solitary plasmacytoma of the bone and solitary extramedullary plasmacytoma. Solitary plasmacytoma of the mesentery is extremely rare, reported only in a handful of cases. Case Presentation. A 47-year-old man with nonspecific abdominal complains was found to have an ill-defined mass on his mesenteric root. Laparoscopic biopsy and stepwise histopathological examination revealed a mesenteric plasmacytoma, and extensive imaging and laboratory investigations led to the diagnosis of the solitary mesenteric plasmacytoma. The patient underwent definitive radiotherapy and remains under remission one year later. Discussion. Plasma cell dyscrasias include a variant of proliferative disease, characterized by clonal expansion of bone marrow plasma cells, producing a massive quantity of monoclonal immunoglobulin called paraprotein or M-protein. Solitary extramedullary plasmacytoma accounts for only 3–5% of all plasma cell neoplasms. Meticulous adherence to the established diagnostic criteria helps the clinician to set the correct, yet very unusual and unexpected diagnosis.